Is there “too much finance” in central and eastern european countries? - Grabowski, Wojciech; Maciejczyk-Bujnowicz, Iwona (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
In this paper, the parameters of the growth regression, including different variables measuring the degree of financial development for the Central and Eastern European countries are estimated. Next, the optimal values of specific variables measuring the level of financial development are calculated. The results of the empirical investigation indicate that countries with more stable financial markets and institutions and greater access to them grew faster in the period 2001-2015. The results reflecting the impact of the financial deepening on economic growth are more ambiguous. In the pre-crisis period, the relationship between the depth of financial institutions and economic growth turned out to be insignificant. After 2007, countries with moderate values (about 60%) of this coefficient recorded higher rates of growth in real GDP. A U-shaped relationship between the depth of financial markets and economic growth was identified. However the optimal level of development of stock markets was much higher in 2001-2007 than after the Lehman Brothers bankruptcy
Argumenta Oeconomica, 2020, Nr 2 (45), s. 5-30
Keywords: financial system; economic growth; dynamic panel models; GMM estimator